2015
DOI: 10.1149/2.0031512eel
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Alkaline Electrolyte System for Al-Air Battery

Abstract: The performance of Al-air batteries in 4 M NaOH containing ZnO or ZnO/cetyl trimethyl ammonium bromide (CTAB) hybrid inhibitor is studied by constant current discharge test. The characteristics of aluminum anodes after discharge are investigated by scanning electron microscopy (SEM), and energy dispersive analysis of X-ray (EDAX). The corrosion behavior of aluminum electrodes in 4 M NaOH containing ZnO or ZnO/CTAB is studied by means of hydrogen collection and potentiodynamic polarization. SEM and EDAX results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…However, the strong corrosion and hydrogen evolution of Al as an amphoteric metal in alkaline solution greatly reduces the coulombic efficiency of the anode and causes fuel loss in the open-circuit state. 137,[156][157][158] The alkaline electrolyte easily reacts with CO 2 in the air and deteriorates. 159 Despić et al took the lead in applying the NaCl-based electrolyte in the Al-air battery and foresaw two difficulties.…”
Section: Development Of Nacl-based Electrolytes For Metal-air Batteriesmentioning
confidence: 99%
“…However, the strong corrosion and hydrogen evolution of Al as an amphoteric metal in alkaline solution greatly reduces the coulombic efficiency of the anode and causes fuel loss in the open-circuit state. 137,[156][157][158] The alkaline electrolyte easily reacts with CO 2 in the air and deteriorates. 159 Despić et al took the lead in applying the NaCl-based electrolyte in the Al-air battery and foresaw two difficulties.…”
Section: Development Of Nacl-based Electrolytes For Metal-air Batteriesmentioning
confidence: 99%
“…Therefore, hybrid corrosion inhibitors are put forward to overcome the problem caused by a single inorganic inhibitor. Extensive research has verified that a hybrid corrosion inhibitor could combine the advantages of organic and inorganic inhibitors, which not only provides a protective layer to reduce the active sites of self-corrosion but also stabilizes and enhances the film by the adsorption of organic inhibitors. , Studies have shown that cetyltrimethylammonium bromide and poly­(ethylene glycol) di- acid could greatly improve the deposition of metallic zinc on the Al interface to restrain self-corrosion and amend the electrochemical properties of a pure aluminum anode (99.999 and 99.9995%). , It is found that carboxymethyl cellulose and organic acids adsorbed on Zn and Al surfaces form RCOO-Al and RCOO-Zn composite protective films to improve the electrochemical performance of the AA5052 alloy and porous Al foam (95.17%) anode. , However, the reported studies mainly concentrated on the electrochemical characterization of Al anodes, and hence, there is limited understanding on the electrode/electrolyte interface.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Studies have shown that cetyltrimethylammonium bromide and poly-(ethylene glycol) di-acid could greatly improve the deposition of metallic zinc on the Al interface to restrain self-corrosion and amend the electrochemical properties of a pure aluminum anode (99.999 and 99.9995%). 21,22 It is found that carboxymethyl cellulose and organic acids adsorbed on Zn and Al surfaces form RCOO-Al and RCOO-Zn composite protective films to improve the electrochemical performance of the AA5052 alloy and porous Al foam (95.17%) anode. 23,24 However, the reported studies mainly concentrated on the electrochemical characterization of Al anodes, and hence, there is limited understanding on the electrode/electrolyte interface.…”
Section: Introductionmentioning
confidence: 99%
“…At present, there are many research institutes around the world having studied the application of aluminum air batteries in various fields . However, these researches on aluminum air batteries mainly focus on the improvement of anticorrosion performance of aluminum alloy, the improvement of waterproof and gas permeability of oxygen positive electrode, the improvement of catalyst activity, the development of different types of liquid and gel electrolytes, and the improvement of various inhibitors' effects . The research on the performance parameters of aluminum air battery, such as the open‐circuit voltage (OCV), is still relatively rare.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12] However, these researches on aluminum air batteries mainly focus on the improvement of anticorrosion performance of aluminum alloy, the improvement of waterproof and gas permeability of oxygen positive electrode, the improvement of catalyst activity, the development of different types of liquid and gel electrolytes, and the improvement of various inhibitors' effects. [13][14][15][16][17][18][19] The research on the performance parameters of aluminum air battery, such as the open-circuit voltage (OCV), is still relatively rare. The OCV is an approximation of the battery electromotive force, and in current actual test, the electromotive force is measured by the OCV value.…”
Section: Introductionmentioning
confidence: 99%